Renal Artery Rupture in Association With Fibromuscular Dysplasia. (14th March 2018) - Akel, Tamer; Elsayegh, Suzanne
Fibromuscular dysplasia is a noninflammatory arteriopathy of unknown etiology that affects medium-sized arteries. Although patients affected with it are often asymptomatic, some might have recurrent catastrophic events that depend mainly on the arterial bed involved. The most worrisome vascular complications of the disease are aneurysmal rupture and arterial dissection. Herein, we report a case of a 49-year-old woman who presented with sudden-onset abdominal pain without any inciting factors. She was found to have active blood extravasation from a capsular branch of the renal artery that happened spontaneously. Angiography revealed fibromuscular dysplasia in the renal arteries without any obvious aneurysms. To our knowledge, this is the first case in the literature describing such an event. In this article, we also review the possible underlying pathology behind such an event.